The link between depression and diabetes: the search for shared mechanisms. Issue 6 (June 2015) - Moulton, Calum D; Pickup, John C; Ismail, Khalida
Summary: Depression is twice as common in people with type 1 or type 2 diabetes as in the general population, and is associated with poor outcomes. Evidence is growing that depression and type 2 diabetes share biological origins, particularly overactivation of innate immunity leading to a cytokine-mediated inflammatory response, and potentially through dysregulation of the hypothalamic-pituitary-adrenal axis. Throughout the life course, these pathways can lead to insulin resistance, cardiovascular disease, depression, increased risk of type 2 diabetes, and increased mortality. Proinflammatory cytokines might directly affect the brain, causing depressive symptoms. In type 1 diabetes, mediators of depression are not well studied, with research hindered by inconsistent definitions of depression and scarcity of observational, mechanistic, and interventional research along the life course. Despite few studies, evidence suggests that familial relationships and burden of a lifelong disorder with an onset early in personality development might contribute to increased vulnerability to depression. Overall, longitudinal research is needed to identify risk factors and mechanisms for depression in patients with diabetes, particularly early in the life course. Ultimately, improved understanding of shared origins of depression and diabetes could provide the potential to treat and improve outcomes of both disorders simultaneously. These shared origins are targets for primary prevention of type 2 diabetes.